A plasma-based DNA test for quantification of disease burden in acute myeloid leukemia patients undergoing bone marrow transplantation - Yuxuan Wang; Jiajun Xie; Sergiu Pasca; Maria Popoli; Janine Ptak; Lisa Dobbyn; Natalie Silliman; Suman Paul; Richard J. Jones; Mark J. Levis; Samuel D. Curtis; Christopher Douville; et al. (Proceedings of the National Academy of Sciences, 2026)
Allogeneic hematopoietic cell transplantation is the only curative option for many patients with acute myeloid leukemia (AML). In the current study, we designed and implemented a personalized assay, called v96, incorporating up to 96 mutations in 30 AML patients undergoing transplantation. The assay was performed on DNA derived from cells isolated from the bone marrow as well as in cell-free plasma. All 30 (100%) of patients harbored molecular evidence of residual leukemia during remission that was detectable by the v96 assay, while only 6 (20%) had evidence of disease as assessed by conventional clinical assays. Furthermore, cell-free DNA from plasma proved to be more sensitive than DNA from cells of the bone marrow for identifying residual leukemia. The median number of mutants was 352-fold higher in plasma taken prior to transplantation for patients who relapsed compared to those who did not relapse. At 2 mo posttransplantation, 27 of the 30 patients still harbored detectable leukemia as assessed by the v96 assay. Twenty-two of these patients had a subsequent decrease in leukemic burden assessed by the v96 assay. In the majority of them (20 of 22 patients), the decrease occurred only after immunosuppression was discontinued, supporting a graft-versus-leukemia effect. These results document the feasibility of using a relatively large panel of carefully chosen mutations and a highly specific assay as noninvasive markers of therapeutic response in AML patients, minimizing the need for multiple bone marrow biopsies.